Metal-free π-conjugated hybrid g-C3N4 with tunable band structure for enhanced visible-light photocatalytic H2 production. (10th October 2021) - Huang, Hengming; Hu, Kan; Xue, Chen; Wang, Zhiliang; Fang, Zhenggang; Zhou, Ling; Sun, Menglong; Xu, Zhongzi; Kou, Jiahui; Wang, Lianzhou; Lu, Chunhua
Graphical abstract: Highlights: A metal-free π-conjugated hybrid g-C3 N4 photocatalyst with tunable band structure was prepared by a one-pot bottom-up method. The hybrid g-C3 N4 is revealed to be a compound of periodic tri-s-triazine units grafted with N-doped graphene fragments. The π-conjugated electron coupling in the hybrid g-C3 N4 promotes the separation of photo-induced charge carriers. Compared with pristine g-C3 N4, the visible-light H2 production activity of the optimized sample is enhanced by 253 %. Abstract: Development of low-cost and efficient photocatalytic materials with visible-light response is of urgent need for solving energy and environmental problems. Here, a metal-free two-dimensional (2D) π-conjugated hybrid g-C3 N4 photocatalyst with tunable band structure was prepared by a novel one-pot bottom-up method based on a supersaturated precipitation process of urea and triethanolamine (TEOA) solution. The microstructure of the hybrid g-C3 N4 is revealed to be a compound of periodic tri-s-triazine units grafted with N-doped graphene (GR) fragments. From experimental evidence and theoretical calculations, the two different π-conjugated fragments in the hybrid g-C3 N4 material are proved to construct a 2D in-plane junction structure, thereby expanding the light absorption range and accelerating the interface charge transfer. The π-conjugated electron coupling in the 2D photocatalyst eliminates the grain boundary effect, and the coupled highest occupied molecular orbital (HOMO) effectively promotes the separation of photo-induced charge carriers. Compared with the g-C3 N4 prepared by the conventional method, the visible-light H2 production activity of the optimized sample is enhanced by 253 %. This work provides a new strategy of constructing metal-free g-C3 N4 hybrids for efficient photocatalytic water splitting.